2006
DOI: 10.1002/anie.200502731
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Core–Shell Particles as Carriers for Ag Nanoparticles: Modulating the Catalytic Activity by a Phase Transition in Networks

Abstract: Nanoreactors: Metal nanoparticles must be stabilized with carrier systems against aggregation if they are to have applications in catalysis. One such system, a thermosensitive network of poly(N‐isopropylacrylamide) that surrounds a polystyrene core, enables control over the catalytic activity of the nanoparticles through a phase transition and leads to applications as a controllable nanoreactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
548
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(576 citation statements)
references
References 46 publications
(24 reference statements)
23
548
0
Order By: Relevance
“…43,44,[48][49][50][51] It is important to note that except for our recent report, 21 there was no example available in the literature where Os NPs were used for the catalysis reaction of the organic nitro compounds, so we compared our catalytic efficiency with other noble metals like Au and Ag. 43,44,[48][49][50][51] The anisotropic Au NPs also used as a catalyst for the 4-NA reduction and the rate constant value were found to be 2.083 Â 10 À2 min À1 . 2 In our previous report taking Os NCs in DNA as scaffold, we observed the first order catalytic reaction rate 3.87 Â 10 À2 min À1 for first 6 min and 0.45 min À1 for later 8 min.…”
Section: Catalysis Study On the Reduction Of 4-na Using Os Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44,[48][49][50][51] It is important to note that except for our recent report, 21 there was no example available in the literature where Os NPs were used for the catalysis reaction of the organic nitro compounds, so we compared our catalytic efficiency with other noble metals like Au and Ag. 43,44,[48][49][50][51] The anisotropic Au NPs also used as a catalyst for the 4-NA reduction and the rate constant value were found to be 2.083 Â 10 À2 min À1 . 2 In our previous report taking Os NCs in DNA as scaffold, we observed the first order catalytic reaction rate 3.87 Â 10 À2 min À1 for first 6 min and 0.45 min À1 for later 8 min.…”
Section: Catalysis Study On the Reduction Of 4-na Using Os Ncsmentioning
confidence: 99%
“…22 In the present study we observed that the reaction rate was 0.26 min À1 which was the highest ever reported for Os NPs as a catalyst and much superior to other noble metals like Au or Ag. 2,22,43,44,[48][49][50][51] Apart from 4-NA, we also checked our catalysis reaction with other nitro compounds like 4-NP, 2-NP, 2-NA, etc., and in all cases the expected catalysis reduction taking place and the reaction were completed in different time scales. Table S1 (in the ESI †) shows the different nitro compounds tested and the corresponding time required for the full reduction.…”
Section: Catalysis Study On the Reduction Of 4-na Using Os Ncsmentioning
confidence: 99%
“…1 Particularly, AgNPs exhibit electrochemical, 2 catalytic, 3 antimicrobial 4 and optical 5 properties that make them especially interesting in electronic, catalysis and sensors fields. [6][7][8][9][10] These properties, as in other kind of metal NPs, are related with their sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples realizing these described concepts are based on immobilized enzymes [91][92] or catalytically active metal nanoparticles embedded in microgels. [92][93][94] …”
Section: Microgels For Loading and Release Applicationsmentioning
confidence: 99%